MENINGKATKAN KEMAMPUAN KONEKSI MATEMATIK DAN SELF EFFICACY SISWA SMP MELALUI PENDEKATAN BRAIN BASED LEARNING - Rusyani Zain, Ella Nurlatifah (Universitas Suryakancana, 2018)
This research is based on facts in the field indicating that the mathematical connection ability of self-efficacy of students has not been in accordance with expectations. This study aims to improve the ability of mathematical connections and self-efficacy of students using the Brain Based Learning approach. This research method is an experimental method with the population of all SMPN students in Cianjur District and a sample of two classes of students SMPN 2 Cipanas randomly selected class. Instruments used are test instruments and non-test. The result of the research shows that the improvement of mathematical connection ability and self-efficacy of students using Brain Based Learning approach is better than using ordinary learning. this study has an association for both variables with moderate criteria.Â Keywords: Brain Based Learning, Mathematical Connection, Self-Efficacy.Â